Age-related outcomes in heart failure with mildly reduced ejection fraction - Reinhardt, Marielen; Schupp, Tobias; Behnes, Michael; Lau, Felix; Schmitt, Alexander; Abel, Noah; Akın, Muharrem; Rusnak, Jonas; Akın, Ibrahim; Weidner, Kathrin (Journal of Clinical Medicine, 2024)
Objective: This study investigates age-related differences and outcomes in patients hospitalized with heart failure with a mildly reduced ejection fraction (HFmrEF). Background: The characterization of patients with HFmrEF and the prognostic value of age has rarely been investigated. Methods: Patients with HFmrEF were retrospectively included at one institution between 2016 and 2022. The distribution of HF aetiology and prognostic outcomes were investigated comparing patients with ≤40, >40 to ≤60, >60 to ≤80, and >80 years of age. The primary endpoint was long-term all-cause mortality. Kaplan-Meier and multivariable Cox proportional regression analyses were applied for statistics. Results: For the present study, 2184 patients with HFmrEF with a median age of 76 years were included. Non-ischemic cardiomyopathy was the most common HF aetiology in patients <40 years of age, whereas patients with 60-80 years of age (60.2%) and >80 years of age (58.2%) had the higher rates of ischemic cardiomyopathies. The risk of long-term all-cause mortality at 30 months was highest in patients with >80 years of age (HR = 2.167; 95% CI 1.928-2.436; p = 0.001), even after multivariable adjustment. Furthermore, patients with >80 years of age had the highest risk of HF-related rehospitalization (HR = 1.529; 95% CI 1.293-1.807; p = 0.001). Conclusions: Ischemic cardiomyopathy represents the most common cause of HF in elderly patients with HFmrEF, whereas younger patients were more likely to suffer from non-ischemic HF aetiologies. Increasing age was an independent predictor of long-term all-cause mortality in patients hospitalized with HFmrEF.